2008
DOI: 10.1002/adfm.200800165
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineered Carboxymethylchitosan/Poly(amidoamine) Dendrimer Nanoparticles for Intracellular Targeting

Abstract: Novel highly branched biodegradable macromolecular systems have been developed by grafting carboxymethylchitosan (CMCht) onto low generation poly(amidoamine) (PAMAM) dendrimers. Such structures organize into sphere‐like nanoparticles that are proposed to be used as carriers to deliver bioactive molecules aimed at controlling the behavior of stem cells, namely their proliferation and differentiation. The nanoparticles did not exhibit significant cytotoxicity in the range of concentrations below 1 mg mL−1, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 60 publications
12
80
1
Order By: Relevance
“…Although not strongly statistically significant (P = 0.103, ANOVA), a visible increase in the rate of endosome formation occurs after the exposure of astrocytes to NPs. In contrast to previous studies where the internalization of the CMCht/ PAMAM dendrimer NPs was detected only after 12 h of incubation, reaching the maximum intracellular load 24 h after exposure, 13 this study revealed changes in vesicle trafficking immediately upon exposure of astrocytes to NPs. These results suggest that the presence of NPs per se may stimulate endocytosis.…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…Although not strongly statistically significant (P = 0.103, ANOVA), a visible increase in the rate of endosome formation occurs after the exposure of astrocytes to NPs. In contrast to previous studies where the internalization of the CMCht/ PAMAM dendrimer NPs was detected only after 12 h of incubation, reaching the maximum intracellular load 24 h after exposure, 13 this study revealed changes in vesicle trafficking immediately upon exposure of astrocytes to NPs. These results suggest that the presence of NPs per se may stimulate endocytosis.…”
Section: Resultscontrasting
confidence: 51%
“…56 CMCht-grafted PAMAM dendrimers have been suggested to follow unspecified endocytotic routes. 13 However, studies involving inhibitors of endocytosis have shown that inhibitors are not selective, influencing more than a single pathway. 57 Therefore, complementary methods are crucial to better understand the mechanisms of cellular NP trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently novel water-soluble nanoparticles that consist of a PAMAM dendrimer core with grafted carboxymethyl chitosan chains were successfully synthesized [120]. The non-cytotoxicity and successful internalization of these dendrimer nanoparticles by two different types of cells, i.e., cell lines and primary cultures, was demonstrated in this work.…”
Section: Drug Deliverymentioning
confidence: 93%